EPITOME OF MANAGEMENT, PHILOSOPHY, AND SCIENCE: ALTERNATIVE RESEARCH AGENDAS - Ríos, Francisco Ballina (ShodhGyan-NU: Journal of Literature and Culture Studies, 2026)
This article aims to provide a synopsis of a very extensive work, highlighting the relationship between administration, philosophy, and science, using critical hermeneutics as its methodology to promote new research agendas. In an increasingly fragmented world, administrative and organizational theory faces epistemological challenges characterized by the rise of communication technologies and Artificial Intelligence, where complex patterns and behaviors emerge that confront managers and executives daily. The paradigms arising from these new research agendas are necessary and even indispensable as points of arrival, but at the same time, they must be starting points for other theoretical constructions. Understanding reality requires a creative and innovative spirit, with new ecological, economic, and social perspectives